NURSE LED PATIENT EDUCATION ON HEALTH OUTCOMES AND PATIENT SATISFACTION AT MEDICARE HOSPITAL MULTAN (Journal of Medical & Health Sciences Review, 2025)
Background: Effective patient education is a critical component of nursing care, influencing health outcomes, self-care behaviors, and patient satisfaction. Nurse-led educational interventions have demonstrated positive effects in managing chronic diseases, yet their implementation and impact in tertiary care settings in Multan remain underexplored.Objective: To evaluate the effect of structured nurse-led patient education on health outcomes and patient satisfaction among adult patients at Medicare Hospital Multan.Methods: A quasi-experimental pre-test/post-test design was employed, involving 120 adult patients with chronic or acute conditions. Participants received structured nurse-led education covering disease understanding, medication adherence, lifestyle management, and symptom recognition. Data on patient knowledge, self-care behaviors, clinical indicators (blood pressure, fasting blood glucose, BMI), and patient satisfaction were collected pre- and post-intervention using validated tools. Data were analyzed using descriptive and inferential statistics, including paired t-tests and correlation analyses, with significance set at p < 0.05.Results: Post-intervention, significant improvements were observed in knowledge scores (10.5 ± 3.2 to 16.8 ± 2.5, p < 0.001), self-care behaviors (5.2 ± 1.8 to 8.1 ± 1.2, p < 0.001), and clinical outcomes, including systolic blood pressure (145 ± 12 to 132 ± 10 mmHg, p < 0.001), diastolic blood pressure (92 ± 8 to 85 ± 6 mmHg, p < 0.001), and fasting blood glucose (160 ± 25 to 130 ± 20 mg/dL, p < 0.001). Patient satisfaction scores also increased significantly (15.5 ± 2.3 to 22.7 ± 1.8, p < 0.001).Conclusion: Structured nurse-led patient education significantly enhances patient knowledge, self-care behaviors, clinical outcomes, and satisfaction. Integrating nurse-led educational programs into routine care can improve disease management and patient-centered care in tertiary hospital settings.